Implementation of Scientific and Standard Approaches to PAI Learning in the Formation of Student Morals - Hendri Kurniadi; Wawan Wahyudin; Nana Surya Permana (Formosa Journal of Sustainable Research, 2022)
The formation of morals is very important for every human being, starting from the age of the child, because it is the root in fortifying children when dealing with the environment. The formation of this character in students can be done one of them through learning, because in addition to making students master competence, it is also packaged to instill good values, and make it a good behavior. This study used a qualitative approach with descriptive analytical methods in the form of observations, interviews and documentation. The collected data were then analyzed using descriptive and inductive methods. Descriptive method is a discussion method that seeks to describe a symptom, event, and event that occurred during the study. The results of this study are that the scientific approach and PAKEM are very appropriate to be implemented in PAI learning, especially to make it easier for students to understand material that is abstract in nature. This thesis concludes that there are three benefits of implementing a scientific approach and PAKEM, namely: 1) to become an interesting and concrete learning model, 2) to familiarize students with good attitudes and behavior, and 3) to involve students actively. This conclusion supports the theory of the scientific approach and PAKEM which aims not only to increase intellectual reasoning and the ability to solve problems independently, but also to form commendable morals as a result of developing spiritual and social attitudes